Learning at old age: a study on winter bees - Behrends, Andreas; Scheiner, Ricarda (Frontiers in Behavioral Neuroscience, 2010)
Ageing is often accompanied by a decline in learning and memory abilities across the animal kingdom. Understanding age-related changes in cognitive abilities is therefore a major goal of current research. The honey bee is emerging as a novel model organism for age-related changes in brain function, because learning and memory can easily be studied in bees under controlled laboratory conditions. In addition, genetically similar workers naturally display life expectancies from six weeks (summer bees) to six months (winter bees). We studied whether in honey bees, extreme longevity leads to a decline in cognitive functions. Six-month-old winter bees were conditioned either to odours or to tactile stimuli. Afterwards, long-term memory and discrimination abilities were analysed. Winter bees were kept under different conditions (flight /no flight opportunity) to test for effects of foraging activity on learning performance. Despite their extreme age, winter bees did not display an age-related decline in learning or discrimination abilities, but had a slightly impaired olfactory long-term memory. The opportunity to forage indoors led to a slight decrease in learning performance. This suggests that in honey bees, unlike in most other animals, age per se does not impair associative learning. Future research will show which mechanisms protect winter bees from age-related deficits in learning.